Influence of nutrient and weed management on weed dynamics and productivity of upland rice (Oryza sativa) - PADHAN, SMRUTI RANJAN; RATHORE, SANJAY SINGH; PRASAD, S M; SINGH, R K; SHEKHAWAT, KAPILA (The Indian Journal of Agricultural Sciences, 2021)
The field experiment was conducted during kharif 2019 at ICAR-CURRS-NRRI at Hazaribagh, Jharkhand. The experiment was conducted to evaluate precision nutrient management and weed management practices for achieving minimum weed menace and maximum crop productivity. Under precision nutrient management, Nutrient Expert ® guided NPK recorded lesser weed density (7.76, 8.07 and 8.62) at all three stages. Pendimethalin fb hand weeding resulted in comparatively lesser weed density (7.72, 7.29 and 7.34 at 25, 60 DAS and at harvest). Nutrient Expert ® guided NPK resulted in maximum grain yield (3.63 t/ha), followed by Leaf Colour Chart (LCC) guided N + Full P & K (3.41 t/ha), which was significantly higher over RDF. Among the weed management aspects, pendimethalin fb hand weeding and bispyribac-Na were observed with significantly higher grain yield (4.09 and 3.79 t/ha). Hence Nutrient Expert Â® guided NPK and pendimethalin fb hand weeding can be recommended for better weed management and enhanced productivity.